Usage and features of cultivation of sphagnum moss in a biotechnological system for natural filtration, purification of air in urban conditions - Инелова, З.А.; Yermekov, А.Е.; Yedilkhan, D. (Fundamental and Experimental Biology, 2022)
This article presents the results of a study of a literature review on the use of mosses as natural filters for air purification in polluted locations; provides information on the features of the cultivation of sphagnum moss by vertical and horizontal methods in the future design of a biotechnological system; describes the necessary conditions to achieve the maximum effect of air purification using this type of plant culture. The study results will be used in the development of unique equipment, namely a pilot prototype of a biotechnological system — a filter using sphagnum moss as a natural filter for air purification in a certain area. This development involves the use of automated control systems to create artificial conditions for plant culture — moss, which, for natural reasons, cannot exist in urban environments. In the long term, a biotechnological filter will effectively clean the air, cool the environment and reduce the noise level in those locations where it is impossible to plant many trees due to large buildings. Currently, groups of scientists around the world are conducting research and experimental development of various solutions, including technologies that can significantly im-prove the urban environment using natural filters. Using mosses as a natural filter will absorb fine dust, purify the air, and create a favorable space.